Use of Cobalt–Chromium 64 Wires Surpass Evolve for the Treatment of Remnant Intracranial Aneurysms: A Subanalysis From the SEASE International Registry - Mahmoud Dibas; Juan Vivanco‐Suarez; Demetrius Klee Lopes; Ricardo A. Hanel; Aaron Rodriguez‐Calienes; Gustavo M. Cortez; Johanna T. Fifi; Alex Devarajan; Gabor Toth; Thomas E. Patterson; David Altschul; Vitor M. Pereira; et al. (Stroke: Vascular and Interventional Neurology)
Background The use of the Surpass Evolve flow diverter for intracranial aneurysms (IAs) has shown promising results, but there are no studies that evaluated its effectiveness for remnant previously treated IAs. This study aimed to evaluate the safety and effectiveness of Surpass Evolve for previously treated IAs. Methods This subanalysis is derived from the SEASE (Safety and Effectiveness Assessment of Surpass Evolve) registry, a retrospective, multicentric, international cohort conducted across 15 academic institutions in North America and Europe between July 2020 and October 2022. Adult patients undergoing Surpass Evolve implantation for single saccular IAs were grouped into those with previously treated IAs by coiling or intrasaccular‐devices and those with untreated IAs. Baseline characteristics and outcomes were compared. Results This study included 257 patients with IAs. Of those, 66 patients had previously treated IAs (median time between diagnosis and initial treatment and retreatment: 6.28 months), and 191 patients had untreated IAs. Of the 246 patients with 10.5 months of imaging follow‐up, the core lab adjudicated complete occlusion was less in previously treated IAs compared with untreated IAs (59.7% versus 72.3%; adjusted odds ratio, 0.43 [95% CI, 0.21–0.88]; P = 0.022). Furthermore, we found similar rates of adequate occlusion between previously treated IAs (83.9%) and untreated IAs (82.1%, P = 0.746). There was no difference in rates of major stroke (1.5% versus 2.6%, P>0.999), mortality (1.5% versus 1.0%, P>0.999), modified Rankin Scale score 0–2 (93.7% versus 95.7%, P = 0.504), and retreatment (1.6% versus 3.3%, P = 0.684) between the 2 groups. Conclusion Our results revealed reasonable rates of occlusion and an acceptable safety profile for the use of Surpass Evolve to treat previously treated IAs. Future prospective studies with longer follow‐ups are warranted to explore the findings further.